“It's Never Too Early”: Preconception Care and Postgenomic Models of Life - Pentecost, Michelle; Meloni, Maurizio (Frontiers in Sociology, 2020)
In this article, we are concerned with the expanded public health interest in the “preconception period” as a window of opportunity for intervention to improve long-term population health outcomes. While definitions of the “preconception period” remain vague, new classifications and categories of life are becoming formalized as biomedicine begins to conduct research on, and suggest intervention in, this undefined and potentially unlimited space before conception. In particular, we focus on the burgeoning epidemiological interest in epigenetics and Developmental Origins of Health and Disease (DOHaD) research as simultaneously a theoretical spyglass into postgenomic biology and a catalyst toward a public health focus on preconception care. We historicize the notion that there are long-term implications of parental behaviors before conception, illustrating how, as Han and Das have noted, “newness comes to be embedded in older forms even as it transforms them” (2015, p. 2). We then consider how DOHaD frameworks justify a number of fragmented claims about preconception by making novel evidentiary assertions. Engaging with the philosophy of Georges Canguilhem, we examine the relationship between reproductive risk and revised understandings of biological permeability, highlighting and discussing some of the epistemic and political implications of emerging claims in postgenomics.